Multi-criteria evaluation in website quality determination - Zulzalil, Hazura; Abd Ghani, Abdul Azim; Selamat, Mohd Hasan; Mahmod, Ramlan (2012)
The evaluation of Website is a multi-criteria problem, which involves combining several measures into a single value through an aggregation operator. To the best of our knowledge, none of the evaluation approaches study the existence of relationships between the quality criteria. All of the evaluation approaches just simply assume the quality criteria are independent to each other to make the aggregation procedure easy. The process of aggregation should take into account dependence between criteria as the criteria are sometimes interacting with each other. This paper discusses the issues of multi-criteria evaluation and highlights the interaction problem between the quality criteria. The idea to incorporate the fuzzy measures in the evaluation procedure has addressed the issue of dependence between criteria. The relationships between quality criteria need to be investigated to identify their positive or negative interaction. The proposed multi-criteria evaluation procedure has allowed the incorporation of interaction exist between the quality criteria to be considered in the aggregation process. The results are also consistent with the additive model approach when no interaction exists.